Structural and Theoretical Studies of 2-amino-3-nitropyridine - N. S. Al-Hokbany; A. A. Dahya; I. Kh. Warad; N. M. Abd El-Salam; S. T. Akriche; M. Rzaiguib; U. Karamac; R. M. Mahfouzc (E-Journal of Chemistry)
Geometrical optimization, spectroscopic analysis, electronic structure and nuclear magnetic resonance of 2-amino-3-nitropyridine (ANP) were investigated by utilizing ab-initio (MP2) and DFT(B3LYP) using 6-311++G(d,p) basis set. Geometrical parameters (bond lengths, bond angles and torsion angles) were computed and compared with the experimental values obtained using X-ray single crystal measurements of the title compound. IR spectra were obtained and assigned by vibrational analysis. Comparing the theoretically calculated values (bond lengths, bond and dihedral angles) using both B3LYP/6-311++G(d,p) and MP2/6-311++G(d,p) methods of calculations with the experimentally determined data by X-ray single crystal measurements, all the data obtained in this investigation were considered to be reliable. The theoretical infrared spectra have been successfully simulated by means of DFT and MP2 levels of calculations. The 1H and 13C nuclear magnetic resonance (NMR) chemical shifts of 2-amino-3-nitropyridine were calculated using the GIAO method in DMSO solution using IEF-PCM model and compared with the experimental data. Intramolecular hydrogen bonding interaction in this compound was investigated by means of the NBO analysis. The calculated HOMO and LUMO energies show that charge transfer occurs within the molecule.